Teachers’ Perceptions, Knowledge, Attitudes, and Practices in Integrating Artificial Intelligence into Arabic Language Teaching - Nur Qomari; Khusnul Khotimah Halimatus Sa'diyah; Ahmad Makki; Moh. Rifqi Habibullah; Gareeb Allah Babiker Mustafa Babiker (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2026)
The rapid integration of Artificial Intelligence (AI) in language education holds transformative potential but faces significant implementation gaps, particularly in Arabic language teaching at the secondary level. This study investigates how teachers’ perceptions, knowledge, attitudes, and gender influence AI adoption in Arabic instruction, addressing a critical gap in which Arabic’s unique linguistic characteristics remain underexplored. Using a quantitative design with total sampling, data were collected from 46 senior high school Arabic teachers through validated instruments measuring four core constructs. The findings reveal that perceptions are the strongest determinant of AI-based teaching practices, outweighing knowledge and attitudes alone. Although teachers demonstrate strong conceptual AI knowledge and generally positive attitudes, practical implementation remains limited due to psychological concerns, insufficient training, and uneven technological access. Notably, gender-based patterns show that female teachers report higher confidence but lower actual AI usage than male teachers, who report greater access to facilities. The study concludes that effective AI integration requires targeted professional development that addresses affective and structural barriers, equitable institutional support, and gender-responsive strategies to translate positive perceptions into sustained classroom practice. Integrasi kecerdasan buatan (AI) dalam pembelajaran bahasa memiliki potensi transformatif namun menghadapi kesenjangan implementasi yang signifikan, terutama dalam pengajaran bahasa Arab di tingkat menengah. Penelitian ini menyelidiki bagaimana persepsi, pengetahuan, sikap, dan gender guru mempengaruhi adopsi AI dalam pembelajaran bahasa Arab, mengatasi kesenjangan kritis di mana karakteristik linguistik bahasa Arab yang unik masih kurang dieksplorasi. Menggunakan desain kuantitatif dengan total sampling, data dikumpulkan dari 46 guru bahasa Arab SMA melalui instrumen tervalidasi yang mengukur empat konstruk inti. Temuan menunjukkan bahwa persepsi muncul sebagai penentu terkuat praktik pengajaran berbasis AI, melampaui pengetahuan dan sikap saja. Meskipun guru menunjukkan pengetahuan konseptual AI yang kuat dan sikap umumnya positif, implementasi praktis tetap terbatas karena kekhawatiran psikologis, pelatihan yang tidak memadai, dan akses teknologi yang tidak merata. Secara mencolok, pola berbasis gender menunjukkan bahwa guru perempuan melaporkan kepercayaan diri lebih tinggi tetapi penggunaan AI aktual lebih rendah dibandingkan guru laki-laki yang melaporkan akses fasilitas lebih besar. Penelitian menyimpulkan bahwa integrasi AI yang efektif memerlukan pengembangan profesional terarah yang mengatasi hambatan afektif dan struktural, dukungan institusional yang adil, serta strategi responsif gender untuk menerjemahkan persepsi positif ke dalam praktik kelas berkelanjutan.